Capacity worth of energy storage systems for renewable power generation plants - Lim, Wei Chan. (2010)
The capacity factor and the cost of electricity of a combination of wind farm and compressed air energy storage (CAES) with a dedicated transmission line are explored in this project. As wind power is intermittent in nature, the use of CAES as the energy storage system could make the power output more controllable. Two scenarios are studied. In the first scenario, the transmission line capacity and the CAES rated output are varied while the wind farm size is fixed to simulate the optimum output in terms of the capacity factor and cost of electricity. It was found that the addition of CAES to the system does not justify the significant increase in cost. In the second scenario the transmission line capacity is fixed and the wind farm is sized larger than the baseline approach. The optimum size for the wind farm was found to be 2 times the transmission capacity, with the capacity factor almost approaching 100 percent and having the lowest cost of electricity production among all the wind farm sizes.